2014
DOI: 10.1111/tpj.12575
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of xylan acetylation suggests xylan may interact with cellulose microfibrils as a twofold helical screw in the secondary plant cell wall of Arabidopsis thaliana

Abstract: The interaction between xylan and cellulose microfibrils is important for secondary cell wall properties in vascular plants; however, the molecular arrangement of xylan in the cell wall and the nature of the molecular bonding between the polysaccharides are unknown. In dicots, the xylan backbone of β-(1,4)-linked xylosyl residues is decorated by occasional glucuronic acid, and approximately one-half of the xylosyl residues are O-acetylated at C-2 or C-3. We recently proposed that the even, periodic spacing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
259
4
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(298 citation statements)
references
References 55 publications
21
259
4
9
Order By: Relevance
“…3). Previous modeling studies show that the preferred conformation for xylan in solution is a twisted 3 1 -fold helical screw conformation (Mazeau et al, 2005;Busse-Wicher et al, 2014), the same as was reported previously for the experimentally determined crystal structure of xylan hydrate (Nieduszynski and Marchessault, 1971). Free energy surfaces for the backbone glycosidic linkage conformations are presented in Figure 4 (for X 6 and XXA 3 XU m X) and Supplemental Figure S9 (for all other glycosidic linkages).…”
Section: Influence Of Regular Substitution Motifs On the Backbone Consupporting
confidence: 60%
See 2 more Smart Citations
“…3). Previous modeling studies show that the preferred conformation for xylan in solution is a twisted 3 1 -fold helical screw conformation (Mazeau et al, 2005;Busse-Wicher et al, 2014), the same as was reported previously for the experimentally determined crystal structure of xylan hydrate (Nieduszynski and Marchessault, 1971). Free energy surfaces for the backbone glycosidic linkage conformations are presented in Figure 4 (for X 6 and XXA 3 XU m X) and Supplemental Figure S9 (for all other glycosidic linkages).…”
Section: Influence Of Regular Substitution Motifs On the Backbone Consupporting
confidence: 60%
“…A regular distribution of glucuronic acids was reported previously in the xylans extracted from softwoods, whereas the pattern in hardwoods seemed to be irregular (Jacobs et al, 2001). Recent studies, however, have shown that glycosidic and acetyl decorations are preferably evenly spaced in specific domains of the xylan backbone (Bromley et al, 2013;Busse-Wicher et al, 2014;Chong et al, 2014), which could sterically allow favorable interactions with the hydrophilic surfaces of cellulose microfibrils (BusseWicher et al, 2016a(BusseWicher et al, , 2016b. Moreover, backbone substitution influences the solubility of hemicelluloses and their macroscopic properties Sternemalm et al, 2008;Pitkänen et al, 2009;Escalante et al, 2012;Bosmans et al, 2014;Littunen et al, 2015).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…8A), which has not been reported in Arabidopsis. There, xylosyl residues were found to be alternatively substituted with acetates (Busse-Wicher et al, 2014). OsTBL2 shares 97% sequence identity with OsTBL1 (Supplemental Fig.…”
Section: Ostbl1 Represents a Xylan O-acetyltransferasementioning
confidence: 99%
“…O domínio fibrilar composto pelas microfibrilas de celulose encontra-se imerso no segundo domínio, formado por uma matriz de polissacarídeos não-celulósicos, as hemiceluloses e as pectinas, que conferem rigidez e resistência à parede (Buckeridge et al, 2000;Cosgrove, 2005). As hemiceluloses são formadas geralmente por um esqueleto de ligações β(1-4) com presença de cadeias laterais, que impedem a formação de estruturas cristalinas (Marriott et al, 2016), formando cadeias longas associadas à celulose através de pontes de hidrogênio (Busse-Wicher et al, 2014). Dependendo da espécie vegetal, as hemiceluloses representam de 20-40% dos polissacarídeos de parede celular (Marriott et al, 2016), podendo apresentar ainda composição variada.…”
Section: Figura 2 Esquema Estrutural Das Paredes Celulares Do Tipo Iunclassified